World of Warcraft chronicle. Volume III - Metzen, Chris (Dark Horse Books, 2018)
"World of Warcraft, Chronicle: Volume III resumes the epic multipart saga of Azeroth as agents of the Burning Legion unleash a mysterious plague of undeath, thrusting the Horde and the Alliance Proudmoore, Thrall, and Illidan Stormrage must decide how much they are willing to sacrifice to save their world, and new lore will be revealed about the characters and events that have shaped the modern history of the Warcraft universe. Featuring art and illustrations by Peter C. Lee, Joseph Lacroix, Roman Kenney, Rob Seville, Cole Eastburn, Stanton Feng, and others, this stunning tome breathes new life into Warcraft's legendary heroes, villains, and locations."--Published website.